Pretreatment method for impurity element analysis of high-purity silicon material and application thereof

Through the pretreatment process of ultrasonic, pyrolysis, grinding and acid treatment, the waste photovoltaic silicon material is processed, which solves the problem of difficulty in removing EVA glue layer and impurities in the prior art, achieves the smoothing and cleanliness of the samples, and improves the accuracy and sensitivity of DSIMS testing.

CN119618768APending Publication Date: 2025-03-14YONGJIANG LAB +2
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411765827.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to completely remove the EVA glue layer and impurities on the surface without damaging the photovoltaic silicon material, resulting in the sample being unable to meet the flatness and cleanliness requirements of DSIMS testing, affecting the accuracy and sensitivity of the detection.

Method used

Through the pretreatment process of ultrasonic, pyrolysis, grinding and acid treatment, the waste photovoltaic silicon material is treated to ensure that the sample surface is flat and bright, and the EVA glue layer and impurities are removed to make it suitable for DSIMS impurity element analysis.

Benefits of technology

It realizes that while ensuring the integrity of photovoltaic silicon wafer samples, it effectively removes EVA glue layer and impurities on the surface, improves the flatness and brightness of the sample, ensures the accuracy and sensitivity of DSIMS testing, and shortens the detection time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168916010000101
    Figure BDA0005168916010000101
  • Figure BDA0005168916010000111
    Figure BDA0005168916010000111
  • Figure HDA0005168916020000011
    Figure HDA0005168916020000011
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic module recovery treatment, in particular to a pretreatment method for impurity element analysis of a high-purity silicon material and application of the pretreatment method. The pretreatment method comprises the following steps: providing a sample crude product, and carrying out ultrasonic pretreatment on the sample crude product; performing pyrolysis treatment and grinding and polishing treatment on the sample crude product subjected to ultrasonic pretreatment; performing acid treatment on the sample crude product subjected to pyrolysis and grinding and polishing treatment to obtain a sample to be detected; transferring the sample to be detected into a dynamic secondary ion mass spectrometer for impurity element analysis; wherein the sample crude product is of a glass-EVA adhesive layer-photovoltaic silicon wafer-EVA adhesive layer-glass composite layer structure. Through a series of pretreatment processes, the EVA adhesive layer can be effectively separated while the sample is not damaged, and the smoothness and brightness of the surface of the silicon material are remarkably improved, so that the silicon material can be well applied to DSIMS for impurity element analysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic component recycling and processing, and in particular to a pre-processing method for analyzing impurity elements of high-purity silicon materials and an application thereof. Background Art

[0002] Photovoltaic silicon materials are exposed to various working environments for a long time, and their performance is easily degraded due to the introduction of impurity elements. Using DSIMS (dynamic secondary ion mass spectrometer) to test the distribution of impurity elements in discarded photovoltaic silicon materials is of great significance for understanding and optimizing device life. The DSIMS test requires that the surface of the sample to be tested is as smooth and flat as possible, but discarded photovoltaic silicon materials usually use coating etching and other methods to improve their photoelectric conversion efficiency or performance, resulting in the presence of a grid line layer on its surface, which is not flat. In addition, it will be contaminated with various organic substances in the working environment, such as EVA (ethylene-vinyl acetate copolymer) adhesives. If it is directly put into the DSIMS equipment for testing, it will have an adverse effect on the equipment, prolong the test time, and reduce the test accuracy. Therefore, the sample needs to be properly pre-treated to ensure that it can be tested on the DSIMS machine. Summary of the invention

[0003] The existing technology uses laser, grinding, ultrasound, embedding and other technical means to purify and recycle waste photovoltaic materials, but these existing technologies either cannot completely remove the glue layer and impurities on the surface of the silicon wafer, or cause damage to the sample, and the treated sample still cannot be tested on the DSIMS machine. The present invention uses a series of pre-treatment processes such as ultrasound, pyrolysis, grinding and polishing, and acid treatment to ensure that the sample is not damaged while effectively separating the EVA glue layer, and significantly improves the smoothness and brightness of the silicon material surface, so that it can be well applied to DSIMS for impurity element analysis, solving the technical problem that the existing pre-treatment methods cannot prepare samples that meet the DSIMS requirements.

[0004] A first aspect of the present invention provides a pretreatment method for analyzing impurity elements in high-purity silicon materials, the pretreatment method comprising the following steps:

[0005] Providing a crude sample, and performing ultrasonic pretreatment on the crude sample;

[0006] The crude sample after ultrasonic pretreatment is subjected to pyrolysis treatment and grinding and polishing treatment;

[0007] Treating the crude sample after pyrolysis and grinding and polishing with acid to obtain a sample to be tested;

[0008] Transferring the sample to be tested to a dynamic secondary ion mass spectrometer for impurity element analysis;

[0009] In some preferred embodiments, the crude sample is a composite layer structure of glass-EVA adhesive layer-photovoltaic silicon wafer-EVA adhesive layer-glass.

[0010] The pre-treatment method of the present invention is directed to a composite layer structure of glass-EVA adhesive layer-photovoltaic silicon wafer-EVA adhesive layer-glass (such as Figure 1 As shown), the material is usually waste photovoltaic silicon material. When the silicon material is analyzed for impurity elements, although the glass of the outer layer of the material can be removed by heating treatment combined with physical removal means, the EVA layer has extremely high adhesion to the photovoltaic silicon wafer in the middle, and it is difficult to completely peel off the EVA layer without damaging the photovoltaic silicon wafer in the middle. As an elemental component analysis device for solid materials based on an ion source, DSIMS has extremely high requirements for the sample to be tested when performing detection. This is mainly because the working principle of DSIMS is to sputter the sample surface by using a focused primary ion beam to bombard a trace amount of multiple particles, collect the secondary ions with positive or negative charge therein by a mass analyzer, and selectively separate the charged secondary ions according to the charge-to-mass ratio, thereby obtaining the secondary ions and matrix element ions of the element to be tested, and finally collecting and analyzing them by a detector, and finally obtaining information about the composition of the element to be tested on the sample surface and the distribution of concentration with depth. This process requires that the surface of the sample to be tested must be flat and smooth, so that the focused ion beam and the sample test micro-area maintain the same incident angle and ion yield with the sample contact surface during the sputtering process, thereby reducing the impact on data accuracy. If the sample surface is uneven or has defects, it will inevitably affect the focusing and sputtering effect of the ion beam, thereby reducing the accuracy and sensitivity of the analysis; at the same time, the waste photovoltaic silicon material has a rough surface, many pores, a large specific surface area, and the attached EVA glue layer and existing pollutants may cause irreversible damage to DSIMS. The technical core of the present invention is to effectively remove the EVA glue layer on the surface of the photovoltaic silicon wafer while ensuring the integrity of the sample through pyrolysis and grinding and polishing operations, and ensure that the flatness and brightness of the sample surface meet the analysis requirements of DSIMS, thereby realizing the detection and analysis of impurity elements in silicon materials.

[0011] In some preferred embodiments, before the crude sample is subjected to ultrasonic pretreatment, the initial sample is firstly subjected to a splitting operation to obtain an initial sample having a size that meets the requirements; the initial sample is marked and the surface of the initial sample is cleaned to obtain a crude sample for use in the next operation.

[0012] Further preferably, the size of the crude sample is 5 mm 2 -100mm 2 It can be flexibly set according to the specifications of the sample rack. For example, for a 4-hole sample rack, the sample can be split into 8mm×8mm pieces.

[0013] The present invention does not impose any particular limitation on the tool for splitting, as long as it can achieve the purpose of splitting; for example: splitting forceps.

[0014] In some preferred embodiments, the ultrasonic pretreatment comprises: placing the crude sample in an organic solvent for ultrasonic treatment.

[0015] The ultrasonic wave generated by the high-frequency oscillator acts on the waste photovoltaic silicon material. On the one hand, the cavitation effect generated by the ultrasonic wave in the organic solvent can destroy the microstructure of the surface of the crude sample, making it easier for impurities to dissolve from the crude sample and disperse in the solvent; on the other hand, the disturbance effect of the ultrasonic wave helps to promote the mixing and dispersion between the organic solvent and the sample, thereby improving the removal efficiency of impurities; thirdly, the high acceleration and crushing effect of the ultrasonic wave can directly act on the impurity particles, breaking them up and dispersing them in the organic solvent. The synergistic effect of the above three aspects can also promote the penetration and cleaning of the solvent on the surface of the crude sample, further improving the removal effect of impurities.

[0016] Further preferably, the organic solvent includes one or more combinations of acetone, ethanol, isopropanol, chlorinated hydrocarbons, and xylene.

[0017] In some preferred embodiments, the ultrasonic pretreatment comprises: placing the crude sample in an organic solvent 1 and an organic solvent 2 in sequence for ultrasonic treatment.

[0018] More preferably, the organic solvent 1 and the organic solvent 2 are independently selected from acetone or ethanol.

[0019] More preferably, the organic solvent is acetone; and the surface of the crude sample is wiped with a cotton swab dipped in acetone before using the organic solvent for ultrasound.

[0020] More preferably, the second organic solvent is ethanol; and the surface of the crude sample is wiped with a cotton swab dipped in ethanol before using the second organic solvent for ultrasound.

[0021] In some preferred embodiments, the pyrolysis treatment comprises: subjecting the crude sample after ultrasonic pretreatment to pyrolysis treatment; the pyrolysis treatment temperature is 520° C.-550° C., and the pyrolysis treatment time is 5 min-10 min.

[0022] By subjecting the crude sample to high-temperature pyrolysis at 520°C-550°C, the EVA film on its surface and other impurities (such as residual materials of the photovoltaic backplane layer, copper strips, etc.) will undergo a series of physical and chemical changes. The EVA film will gradually decompose at high temperatures, and its polymer molecular chains will break, thereby achieving separation from the silicon material. The present invention has found through research that when the pyrolysis temperature is lower than 520°C, the EVA layer in the waste photovoltaic silicon material will carbonize under the action of high temperature, but it cannot achieve complete pyrolysis; even if the high-temperature treatment time is extended, the EVA layer still exists on the surface of the silicon material. When the pyrolysis temperature is 520-550°C, it only takes 5-10 minutes of pyrolysis, and the glue layer on the surface of the photovoltaic silicon wafer will disappear significantly, and the EVA will be completely pyrolyzed; through metallographic microscopy characterization, there is no EVA glue layer on the surface of the photovoltaic silicon wafer; it is proved that the pyrolysis conditions ensure the complete separation of the EVA glue layer and the silicon material, which provides convenience for the subsequent detection and recovery of the sample.

[0023] The temperature of the pyrolysis treatment can be listed as 520°C, 525°C, 530°C, 535°C, 540°C, 545°C, and 550°C.

[0024] The time of the pyrolysis treatment can be listed as 5 min, 6 min, 7 min, 8 min, 9 min, 10 min.

[0025] In some preferred embodiments, the grinding and polishing treatment includes: performing flattening treatment, grinding treatment and polishing treatment on the crude sample after pyrolysis treatment in sequence to obtain a crude sample with a bright surface.

[0026] Further preferably, during the flattening treatment, the surface of the rough sample is polished using sandpaper with a mesh size of 1000-1600; the mesh sizes can be 1000, 1100, 1200, 1300, 1400, 1500, and 1600; the most preferred size is 1200.

[0027] Further preferably, during the polishing treatment, sandpaper with a mesh size of 2000-2800 is used to polish the surface of the rough sample; the mesh sizes can be 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700 and 2800, and 2400 is the most preferred.

[0028] Further preferably, during the polishing treatment, a polishing agent and a polishing cloth are used in combination to polish the surface of the rough sample under the rotation of a polishing machine; the polishing agent includes a combination of one or more of an adhesive type polishing agent, a metal oxide type polishing agent, an alloy type polishing agent, and a diatomaceous earth type polishing agent.

[0029] Examples of the binder-type polishing agent include wax, grease, paraffin, and resin.

[0030] As examples of metal oxides, aluminum oxide or iron oxide can be cited.

[0031] Examples of the alloy type polishing agent include stainless steel polishing agent, magnesium alloy polishing agent, aluminum alloy polishing agent, and the like.

[0032] In some preferred embodiments, the polishing agent comprises aluminum oxide; more preferably, the particle size of the polishing agent is 0.5um-2um.

[0033] In some preferred embodiments, the rotation speed of the polishing machine during polishing is 100 r / min-200 r / min, and the polishing time is 30 min-60 min.

[0034] Examples of polishing machine rotation speeds include 100 r / min, 110 r / min, 120 r / min, 130 r / min, 140 r / min, 150 r / min, 160 r / min, 170 r / min, 180 r / min, 190 r / min, and 200 r / min.

[0035] When performing the polishing operation, apply the polishing agent to the polishing cloth or the surface of the rough sample, and fix the polishing cloth on the polishing machine, place the rough sample in the polishing machine so that its surface is parallel to the rotating plane of the polishing machine, and start the polishing machine to perform the rotational friction polishing operation.

[0036] The present invention has found that although the EVA adhesive layer adhering to the surface of the silicon material is effectively removed by a specific pyrolysis treatment, the roughness of the crude sample is still relatively high (e.g. Figure 8 As shown). When the roughness of the sample surface is high, on the one hand, the tiny undulations and irregular structures on the sample surface will significantly affect the scattering characteristics of the incident ion beam, causing the incident ions to be reflected and scattered multiple times on the sample surface, thereby reducing the effective excitation depth of the ion beam. On the other hand, the highly rough sample surface is often more likely to adsorb pollutants and form adsorption layers. These pollutants and adsorption layers will hinder the effective collision of the incident ions with the atoms inside the sample, thereby reducing the efficiency of secondary ion generation, and may also cause the incident ion beam to deflect or diffuse, reducing the secondary ion generation density and detection sensitivity. The present invention effectively reduces the roughness of the surface of the rough sample, improves the flatness and brightness of the sample, and further ensures that the sample meets the requirements of DSIMS detection through the sequential operations of flattening, polishing and polishing.

[0037] In some preferred embodiments, the acid treatment is performed twice or more to obtain a sample that can be tested by DSIMS.

[0038] Preferably, the acid selected for the acid treatment includes a combination of one or more of hydrofluoric acid, hydrochloric acid, nitric acid and sulfuric acid.

[0039] Further preferably, the acid treatment includes a first acid treatment and a second acid treatment, the acid used in the first acid treatment is hydrofluoric acid, and the acid used in the second acid treatment is aqua regia (a mixed solution of concentrated hydrochloric acid and concentrated nitric acid).

[0040] Preferably, when the hydrofluoric acid is used for treatment, the crude sample is immersed in the hydrofluoric acid for 30 min to 50 min; more preferably, for 40 min.

[0041] Preferably, when using aqua regia for treatment, the crude sample is immersed in hydrofluoric acid for 3 min-5 min, more preferably 4 min.

[0042] Photovoltaic silicon wafers are usually provided with a series of metal lines on the back to form a gate layer, which helps to disperse the electrons on the entire battery surface. However, the existence of the gate layer causes fine grooves on the back of the silicon wafer, which leads to adsorption and has a negative impact on the vacuum degree of the DSIMS equipment; and the gate layer is often set very precisely, and if strong mechanical elimination means are used, it is easy to damage the silicon wafer sample. The present invention performs acid treatment on the crude sample after grinding and polishing, effectively dissolving and eliminating the oxide layer and rust on the surface of the silicon wafer, so that the surface of the sample is closer to the original smooth state. At the same time, considering that it is necessary to effectively remove impurities on the surface of the sample without excessively corroding the surface of the material, the present invention preferably performs two acid treatments, first soaking the crude sample in hydrofluoric acid, and then soaking the crude sample in aqua regia, to thoroughly remove various impurities remaining on the surface of the crude sample, reduce the influence of impurities on the background value of the instrument, and improve the sensitivity of DSIMS to the detection of impurity elements in silicon materials and the accuracy of the detection results.

[0043] Preferably, each time before the crude sample is subjected to the acid treatment, the crude sample needs to be thoroughly cleaned to ensure that there is no reagent residue from the previous step on the surface of the crude sample; more preferably, ultrapure water is used for ultrasonic cleaning.

[0044] The present invention requires strict implementation of the cleaning operation. After grinding and polishing, ultrapure water cleaning is performed before acid treatment to prevent residual polishing agent on the surface of the sample to be tested from entering the detection equipment and interfering with the test; ultrapure water cleaning is performed after hydrofluoric acid soaking to avoid hydrofluoric acid residue from causing non-uniform corrosion on the surface of the sample to be tested and improve the roughness of the sample; cleaning is performed after soaking in aqua regia to avoid residual acid on the surface of the sample to be tested, which will corrode the sample rack or damage the equipment when the sample to be tested is transferred, thereby ensuring the safety of detection and analysis.

[0045] A second aspect of the present invention provides an application of the above-mentioned pretreatment method in the field of impurity element analysis and detection of high-purity silicon materials.

[0046] Beneficial effects:

[0047] The present invention provides a pretreatment method for analyzing impurity elements in high-purity silicon materials and its application, which has the following advantages:

[0048] (1) The present invention pre-treats the waste photovoltaic silicon material, especially by means of pyrolysis and polishing, so that the surface of the sample to be tested is smooth and bright without any glue layer or impurities, and can be transferred to DSIMS for impurity element testing;

[0049] (2) The preferred pyrolysis temperature of the present invention is 520°C-550°C and the pyrolysis time is 5min-10min, which can ensure that the EVA adhesive layer in the sample is completely separated from the photovoltaic silicon wafer;

[0050] (3) The present invention performs specific grinding, polishing and polishing operations on the crude sample after pyrolysis to ensure that the surface of the silicon material is smooth and flat, so as to improve the sensitivity of DSIMS test analysis, further shorten the detection time and improve the detection efficiency;

[0051] (4) The present invention performs acid treatment on the rough sample after grinding and polishing to further reduce the roughness of the sample and avoid the negative impact of adsorption derived from the gate line layer on the back of the photovoltaic silicon wafer on the vacuum degree of DSIMS.

[0052] (5) This method is simple and easy to operate. After pretreatment, the sample can reach the detection limit in about 70 seconds when it is put into DSIMS, and the accuracy and sensitivity of the detection results are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 .Photos of the original discarded photovoltaic silicon materials (a is a macroscopic image of the sample, b is an enlarged version of the macroscopic image, c is a cross-sectional image of the sample, and d is an enlarged version of the cross-sectional image of the sample; 1 is glass, 2 is an EVA adhesive layer, and 3 is a photovoltaic silicon wafer);

[0054] Figure 2 . Initial sample photos and cross-sectional views (a and b are pictures of the front of the sample at different positions after the glass bonded to the surface is peeled off; c is an enlarged version of picture b; d is a cross-sectional view of the sample);

[0055] Figure 3 .Raman spectrum of the initial sample;

[0056] Figure 4 . Macroscopic morphology of samples R18 and R19 after pyrolysis (left: R18, right: R19);

[0057] Figure 5. Microscopic morphology of samples R18 and R20 after pyrolysis (from left to right: 520℃-5min front-200 times, 540℃-5min front-200 times, 550℃-5min front-200 times);

[0058] Figure 6 . Raman spectra of samples R18 and R20 after pyrolysis (A: R18, B: R19);

[0059] Figure 7 . Microscopic image of the sample before and after grinding and polishing of Example 1 (left: before grinding and polishing, right: after grinding and polishing)

[0060] Figure 8 .Photos of the original photovoltaic material sample, the sample after hydrofluoric acid treatment, and the sample after aqua regia treatment (left: original photovoltaic material sample; middle: sample after hydrofluoric acid treatment; right: sample after aqua regia treatment);

[0061] Fig. 9 . Physical pictures of the original photovoltaic material sample, the sample after hydrofluoric acid treatment, and the sample after aqua regia treatment (in the picture, a is the front of the original photovoltaic material sample, b is the back of the original photovoltaic material sample; c is the front of the sample after hydrofluoric acid treatment, d is the back of the sample after hydrofluoric acid treatment; e is the front of the sample after aqua regia treatment, and f is the back of the sample after aqua regia treatment); Fig.10 .Details of the changes in the sample grid line layer before and after hydrofluoric acid treatment (a: before hydrofluoric acid treatment, 50 times magnification; b: before hydrofluoric acid treatment, 200 times magnification; c: after hydrofluoric acid treatment, 50 times magnification; b: after hydrofluoric acid treatment, 200 times magnification);

[0062] Fig.11 . Sample morphology change diagram during the pretreatment process of Example 1 (a. initial sample, b. sample to be tested after pyrolysis treatment, c. sample to be tested after one cleaning; d. test surface of the sample to be tested after pretreatment; e. back side of the sample to be tested after pretreatment);

[0063] Fig.12 . Initial sample test results;

[0064] Fig.13 .Test results of the sample to be tested after pre-treatment in Example 1. DETAILED DESCRIPTION

[0065] The present invention processes waste photovoltaic silicon materials through a pre-treatment process of ultrasound, pyrolysis, grinding and polishing, and acid treatment. It can effectively remove impurities and obtain a sample to be tested with a smooth, flat and clean surface while ensuring that the photovoltaic silicon wafer sample is not damaged, so that it can enter a dynamic secondary ion mass spectrometer for impurity element analysis, and the detection sensitivity and accuracy are high, and accurate DSIMS test results can be obtained in a relatively short time.

[0066] Example

[0067] This embodiment provides a pre-treatment method for analyzing impurity elements in high-purity silicon materials, comprising the following steps:

[0068] Step (1) providing a crude sample;

[0069] Step (2) performing ultrasonic pretreatment on the crude sample;

[0070] Step (3) pyrolysis treatment of the crude sample after ultrasonic pretreatment;

[0071] Step (4) grinding and polishing the crude sample after pyrolysis treatment;

[0072] Step (5) acid-treating the crude sample after pyrolysis and grinding and polishing to obtain a sample to be tested.

[0073] Transferring the sample to be tested to a dynamic secondary ion mass spectrometer for impurity element analysis;

[0074] The step (1) comprises:

[0075] 1.1 Splitting: Use a diamond marking pen to scribe the initial sample, and then use splitting forceps to split it to prepare an initial sample with a size of 8 mm × 8 mm;

[0076] 1.2 Marking: Use a diamond marking pen to mark the back of the initial sample obtained by splitting, and then wipe the front and back surfaces of the initial sample with a dust-free cotton swab dipped in ethanol to remove the silicon powder remaining on the surface of the initial sample for use in the next step.

[0077] The initial sample is waste photovoltaic silicon material, specifically a composite layer structure of glass-EVA adhesive layer-photovoltaic silicon wafer-EVA adhesive layer-glass.

[0078] The step (2) comprises: using a cotton swab dipped in acetone to wipe the front and back surfaces of the initial sample prepared in step (1) three times, placing the initial sample in acetone for ultrasonication (ultrasonication time is 5 minutes); then taking out the initial sample, using a cotton swab dipped in ethanol to wipe the front and back surfaces of the initial sample three times, and then placing the initial sample in ethanol for ultrasonication (ultrasonication time is 5 minutes), taking out and drying naturally, and waiting for the next step.

[0079] The step (3) comprises: placing the crude sample obtained after the ultrasonic treatment in step (2) on a heating table covered with aluminum foil for pyrolysis treatment, the pyrolysis treatment temperature is 550° C., and the pyrolysis treatment time is 15 minutes. After the pyrolysis is completed, the crude sample is taken to a clean table and naturally cooled to room temperature before being used in the next step.

[0080] The step (4) comprises: taking the crude sample obtained after the pyrolysis treatment in step (3), first using 1200 mesh sandpaper to grind its surface, then using 2400 mesh sandpaper to polish it, and finally using a polishing cloth and a polishing agent to polish it, the polishing agent is 1um aluminum oxide, the polishing speed is set to 150r / min, and the polishing time is 45min.

[0081] The material of the sandpaper is silicon carbide.

[0082] The polishing is performed using a mechanical grinding and polishing machine.

[0083] The acid treatment in step (5) is performed twice to obtain a sample that can be tested by DSIMS. The specific steps include:

[0084] 501 One-time cleaning: The crude sample obtained in step (4) is placed in ultrapure water for ultrasonic treatment 3 times (each ultrasonic treatment lasts 5 minutes, and new ultrapure water is replaced before each ultrasonic treatment); then the crude sample is placed in ethanol for ultrasonic treatment for 5 minutes, and then the crude sample is rinsed with ultrapure water, and then the rinsed sample is placed in ultrapure water for ultrasonic treatment once, and taken out for standby use;

[0085] 502 Previous acid treatment: Soak the crude sample after the first cleaning in concentrated hydrofluoric acid (mass concentration is 40%) for 40 minutes;

[0086] 503 Secondary cleaning: Soak the crude sample after the previous acid treatment in ultrapure water for 1 minute, and then rinse the crude sample with ultrapure water; then, ultrasonicate the rinsed crude sample in ultrapure water for 3 times (5 minutes each time, and replace new ultrapure water before each ultrasonication).

[0087] Post-504 acid treatment: Soak the crude sample after secondary cleaning in aqua regia for 4 minutes; aqua regia is a mixed solution of concentrated hydrochloric acid (mass concentration is 36%) and concentrated nitric acid (mass concentration is 68%) in a volume ratio of 3:1;

[0088] 505 Three-time cleaning: Soak the crude sample after the last acid treatment in ultrapure water for 1 minute, then rinse the crude sample with ultrapure water, and after rinsing, ultrasonicate the crude sample in ultrapure water for 3 times (5 minutes each time, and replace new ultrapure water before each ultrasonication). Then, place the crude sample in ethanol for ultrasonic treatment, and after ultrasonic treatment, wipe the front and back surfaces of the crude sample with a cotton swab dipped in ethanol for 3 times, and then dry it naturally.

[0089] Note: The reagents, tools and conditions used in this example are as follows:

[0090] The ethanol used was an analytically pure product with a concentration of ≥95.0%.

[0091] The acetone used was an analytically pure product with a concentration of ≥99.9%.

[0092] The resistivity of the ultrapure water used is ≥18MΩ*cm, and the number of times of rinsing with ultrapure water during the second and third cleanings is greater than 5 times to ensure that there is no residue; and the waste liquid after the first three rinses should be poured into the acid waste liquid barrel.

[0093] The cotton swab used is a dust-free cotton swab.

[0094] The sampling fixture used in the pretreatment process is a high-temperature resistant clean fixture to ensure that the fixture is preheated and melted during the transfer of the crude sample to prevent the crude sample from sticking and contaminating.

[0095] The ultrasonic frequency involved in the ultrasonic operation is 40 khz.

[0096] And, if not otherwise specified, the solvent of the solution in the present invention is water.

[0097] Performance Testing

[0098] 1. Original samples and initial sample photos

[0099] The original samples of discarded photovoltaic silicon materials were observed using a 3D optical microscope. Figure 1 . Figure 1 a is the macroscopic image of the sample, b is the enlarged version of the macroscopic image, c is the cross-sectional image of the sample, and d is the enlarged version of the cross-sectional image of the sample. Figure 1 It can be seen that the discarded photovoltaic silicon material is a composite layer structure of glass-EVA adhesive layer-photovoltaic silicon wafer-EVA adhesive layer-glass.

[0100] The original sample was heated at 150-200°C and then the glass was removed with tweezers to obtain the initial sample; the photo and cross-sectional view of the initial sample are shown in Figure 2 ; The Raman spectrum of the initial sample is shown in Figure 3 From the Raman spectrum, it can be seen that the initial sample clearly has characteristic peaks of the EVA layer (such as 2600-3000cm -1 ), proving that the initial sample contained an EVA adhesive layer.

[0101] 2. Observation of pyrolysis effect

[0102] The pyrolysis effects of samples under different pyrolysis conditions are compared. The experimental conditions and observation results are recorded in Table 1. The photos of samples R18 and R20 after pyrolysis are shown in Figure 4 From the observation results, it can be seen that the samples were obviously pyrolyzed after being treated at 520℃ and 550℃ for 5min.

[0103] Samples R18 and R20 were further characterized by metallographic microscope. The microscopic characterization photos magnified 200 times are shown in Figure 5 .from Figure 5 It can be seen that there is no EVA adhesive layer on the surface of the sample, proving that the adhesive layer has been completely pyrolyzed.

[0104] The Raman spectra of samples R18 and R19 were further characterized. The characterization results are shown in Figure 6 .

[0105] Table 1

[0106]

[0107]

[0108] Through Table 1 and Figure 4-6 The experimental results show that the waste photovoltaic silicon samples cannot be completely pyrolyzed below 500°C, but the EVA adhesive layer can be effectively pyrolyzed and removed at 520-550°C for 5 minutes; however, carbon impurities still remain on the surface of the sample after removal, and the surface is still relatively rough, making it impossible to perform DSIMS testing, so further processing is still required.

[0109] 3. Observation of grinding and polishing effect

[0110] The samples of Example 1 before and after grinding and polishing were observed under a metallographic microscope, and the microscopic characterization photos magnified 200 times are shown in Figure 7 .from Figure 7 It can be seen that the surface roughness of the sample is significantly reduced after grinding and polishing, and DSIMS testing can be performed.

[0111] 4. Changes in the back grid line layer of the sample after acid treatment

[0112] Compare the results of samples before and after acid treatment, see Figure 8-10 .from Fig.10 It can be seen that hydrofluoric acid treatment can significantly reduce the roughness of the back of the sample, reduce the adsorption caused by the presence of the grid line layer on the surface of the material, avoid the negative impact of the sample on the vacuum degree of the equipment, and help protect the detection equipment. During the experiment, we also tried to replace hydrofluoric acid with hydrochloric acid for treatment. After treatment, the grid line layer of the sample was basically unresponsive.

[0113] 5. Sample surface morphology

[0114] like Fig.11 The figure shows the surface morphology of the sample when the waste photovoltaic silicon material is processed by the pre-treatment method of this embodiment. Fig.11 a is the initial sample, which shows that there is a gate line layer on the surface of the waste photovoltaic silicon material, as well as residual adhesive and impurities; Fig.11b is the sample to be tested after pyrolysis treatment. At this time, the adhesive remaining on the surface of the silicon material has been removed, but it can be seen that there are still impurities on its surface; Fig.11 c is the sample to be tested after one cleaning. At this time, the sample to be tested has been polished, and the impurities on the surface of the material have been removed, and the surface is bright and clean; Fig.11 d. Fig.11 e respectively represent the test surface and back side of the test sample after pre-treatment. It can be seen that after the pre-treatment of this embodiment, the grid line layer, residual adhesive and other impurities on the test surface of the sample have been removed, and the grid line layer on the back side of the test surface of the sample has also been removed, and the test sample has achieved significant cleaning and brightening effects.

[0115] 6.DSIMS test results

[0116] The initial sample after removing the binder and the sample to be tested after pretreatment were respectively subjected to DSIMS to test the bulk concentration of B element in the sample. The test results are shown in Fig.12 , 13 .

[0117] Note: Because the silicon material cannot be tested on the machine if it contains a binder, the initial sample (with a rough surface) with the binder removed is taken for testing as a control during the on-machine test.

[0118] from Fig.12 , 13 It can be seen that the initial sample without the binder reaches the detection limit after 4000s of instrument testing, which takes a long time to test, has extremely low test efficiency and cannot guarantee the accuracy of the test results. However, the sample to be tested after the pretreatment of the present invention can reach the detection limit in about 70s after being tested on the machine, which can be tested quickly, improving test efficiency and test accuracy.

Claims

1. A pretreatment method for impurity element analysis of high-purity silicon material, characterized in that: The pre-treatment method comprises the following steps: Providing a crude sample, and performing ultrasonic pretreatment on the crude sample; The crude sample after ultrasonic pretreatment is subjected to pyrolysis treatment and grinding and polishing treatment; Treating the crude sample after pyrolysis and grinding and polishing with acid to obtain a sample to be tested; Transferring the sample to be tested to a dynamic secondary ion mass spectrometer for impurity element analysis; Among them, the crude sample is a composite layer structure of glass-EVA adhesive layer-photovoltaic silicon wafer-EVA adhesive layer-glass.

2. The pretreatment method for impurity element analysis of high-purity silicon material according to claim 1, characterized in that: The temperature of the pyrolysis treatment is 520° C.-550° C., and the time of the pyrolysis treatment is 5 min-10 min.

3. The pretreatment method for impurity element analysis of high-purity silicon material according to claim 1, characterized in that: The grinding and polishing process includes flat grinding, polishing and buffing.

4. The pretreatment method for impurity element analysis of high-purity silicon material according to claim 3, characterized in that: During the flattening treatment, the surface of the rough sample is polished using sandpaper with mesh sizes of 1000-1600; during the polishing treatment, the surface of the rough sample is polished using sandpaper with mesh sizes of 2000-2800.

5. The pretreatment method for impurity element analysis of high-purity silicon material according to claim 3, characterized in that: During the polishing treatment, the surface of the rough sample is polished by using a polishing agent and a polishing cloth in combination; the polishing agent includes aluminum oxide with a particle size of 0.5um-2um.

6. The pretreatment method for impurity element analysis of high-purity silicon material according to claim 1, characterized in that: The number of times of the acid treatment includes two or more times.

7. The pretreatment method for impurity element analysis of high-purity silicon material according to claim 6, characterized in that: The acid treatment includes a first acid treatment and a second acid treatment. The acid used in the first acid treatment is hydrofluoric acid, and the acid used in the second acid treatment is aqua regia.

8. The pretreatment method for impurity element analysis of high-purity silicon material according to claim 1, characterized in that: The acid used in the acid treatment includes one or more of hydrofluoric acid, hydrochloric acid and nitric acid.

9. The pretreatment method for impurity element analysis of high-purity silicon material according to claim 1, characterized in that: The ultrasonic pretreatment comprises: placing the crude sample in an organic solvent for ultrasonic treatment; the organic solvent comprises acetone and / or ethanol.

10. Application of the pretreatment method according to any one of claims 1 to 9 in the field of impurity element analysis and detection of high-purity silicon materials.

Citation Information

Patent Citations

  • Sample preparation method for GDMS detection, and sample

    CN111537320A

  • Method for detecting content of impurity elements in cobalt

    CN113049671A

  • Separation and recovery method for silicon wafers in waste photovoltaic module

    CN115770780A

  • Photovoltaic module recovery method and device

    CN117046864A

  • Method for preparing silicon nitride from photovoltaic silicon waste

    CN117800296A